Research on green product marketing strategy of enterprise network platform supply chain under digital intelligence driven marketing - Yisun, Chen; Zhang, Xiaoman; Cai, Ning; Mou, Shuangli; Yu, Zong (Scientific Insights and Discoveries Review, 2024)
The digital intelligence-driven marketing technology and online sales service functions of network platforms are conducive to the production and sales of green products. Therefore, this paper constructs a network platform supply chain model consisting of a manufacturer and a platform, considering that the manufacturer invests in green technology to produce products, and the network platform uses consumers' online shopping data to carry out digital intelligence-driven marketing activities. The marketing strategy of the manufacturer and the platform co-marketing green products is studied, and the problem of the manufacturer using the cost-sharing contract to cooperate with the network platform to carry out digital intelligence-driven marketing of green products is considered. The study found that: 1) Optimizing green investment and digital-driven marketing costs, as well as enhancing consumers' sensitivity to green products and digital-driven marketing, are conducive to improving the profitability of network platform supply chain members and the green level of products; 2) Under the agency sales strategy, the commission rate charged by the network platform is the main factor affecting the sales strategy choices of manufacturers and platforms. There is a commission rate threshold that allows manufacturers and platforms to obtain more profits compared to the resale strategy; 3) Under the agency sales and resale strategies, manufacturers can use cost-sharing contracts to effectively incentivize network platforms to sell green products, and there is a cost-sharing threshold that allows manufacturers and network platforms to have the opportunity to obtain Pareto-improved profits. Network platforms charging less commissions and manufacturers sharing larger marketing costs are conducive to achieving a win-win situation in economic and ecological benefits.